1997
DOI: 10.1021/ja963555w
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Circular Dichroism Spectroscopy as a Probe of Geometric and Electronic Structure of Cobalt(II)-Substituted Proteins:  Ground-State Zero-Field Splitting as a Coordination Number Indicator

Abstract: Variable-temperature magnetic circular dichroism (VT MCD) is used as a probe of the ground-state electronic structure in Co(II)-substituted liver alcohol dehyrogenase, carbonic anhydrase, carboxypeptidase, substrate and inhibitor complexes of these enzymes, and four- and five-coordinate Co(II) model complexes. VT MCD was used to determine the magnitude of the ground-state zero-field splitting (ZFS) in these samples. The four-coordinate Co(II) species had ZFS's that ranged from 2.3 to 30 cm-1 and the five-coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
123
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 66 publications
19
123
1
Order By: Relevance
“…For example, X-ray absorption near-edge spectroscopy data from Cd(II) thiolate and imidazole complexes provided insight into the coordination number and nature of coordinating amino acids in the Cd(II)-containing carbonic anhydrase of a marine diatom, which suggested that the active site of this protein employs a tetrahedral coordination geometry and that Cd(II) is bound to a least one cysteine residue. 94 [86][87][88]95 The magnetic exchange coupling from this μ-OH bridged complex was determined to be ferromagnetic and the results from this study can be used to distinguish μ-aqua and μ-hydroxo bridging motifs in Co(II)Co(II) enzyme systems. 86,87 Neves et al were able to synthesise, and spectroscopically and kinetically characterise a dinuclear Fe(III)-Zn(II) complex with a terminal Fe(III)-bound water molecule at a position equivalent to that of the proposed nucleophile in red kidney bean PAP.…”
Section: Biomimetics Of Dinuclear Metallohydrolasesmentioning
confidence: 90%
See 3 more Smart Citations
“…For example, X-ray absorption near-edge spectroscopy data from Cd(II) thiolate and imidazole complexes provided insight into the coordination number and nature of coordinating amino acids in the Cd(II)-containing carbonic anhydrase of a marine diatom, which suggested that the active site of this protein employs a tetrahedral coordination geometry and that Cd(II) is bound to a least one cysteine residue. 94 [86][87][88]95 The magnetic exchange coupling from this μ-OH bridged complex was determined to be ferromagnetic and the results from this study can be used to distinguish μ-aqua and μ-hydroxo bridging motifs in Co(II)Co(II) enzyme systems. 86,87 Neves et al were able to synthesise, and spectroscopically and kinetically characterise a dinuclear Fe(III)-Zn(II) complex with a terminal Fe(III)-bound water molecule at a position equivalent to that of the proposed nucleophile in red kidney bean PAP.…”
Section: Biomimetics Of Dinuclear Metallohydrolasesmentioning
confidence: 90%
“…84 Zero-field splitting, g-tensors and spin states can also be obtained, in addition to magnetic coupling interaction information for dimetallic sites, by analysing variable temperature, variable field (VTVH) data. 84,87,88 MCD studies of Co(II) 2 -GpdQ, have revealed the two distinct binding sites, a 6-coordinate site with high affinity and a 5-coordinate site with low affinity. 38,78 These studies showed that GpdQ exists as a mononuclear resting state enzyme with only the α-site occupied by metal, as evidenced by the single band in the MCD spectrum at 495 nm (typical for 6-coordinate Co(II)).…”
Section: Catalytic Mechanism Of Gpdqmentioning
confidence: 99%
See 2 more Smart Citations
“…This has allowed us, for the first time, to monitor time-resolved MCD resulting from in situ chemical manipulation of a metalloprotein sample. Furthermore, we report the parallel development of an electrochemical cell using a three-electrode configuration with physically separated working and counter electrodes, allowing true potentiometric titration to be performed within the bore of the MCD solenoid.Ó 2011 Elsevier Inc. All rights reserved.Magnetic circular dichroism (MCD) 1 spectroscopy, at ultraviolet-visible and near-infrared wavelengths (185-2000 nm), has proved to be invaluable in the study of metalloproteins containing cofactors such as heme [1][2][3], non-heme iron [4], iron-sulfur clusters [5][6][7][8], cobalt [9,10], nickel [11][12][13], and copper [14,15]. The technique measures the apparent circular dichroism (CD) induced by a magnetic field [16].…”
mentioning
confidence: 99%